Faktor Risiko Kejadian Penyakit Jantung Koroner di Poliklinik RSUD Solok Selatan Tahun 2022 - Nurmaines Adhyka; Eka Trio Effandilus; Anggun Yulia Putri (Jurnal Pembangunan Nagari, 2023)
The prevalence of coronary heart diseases (CHD) in Indonesia based on a doctor's diagnosis was 1.5% (Riskesdas, 2018). Meanwhile, the prevalence of CHD in West Sumatra reached 327,262 people with the highest percentage of 1.8%. The incidence of CHD at South Solok Regional Hospital from January to July 2021 was 492 patients and there were 10 deaths. The purpose of this study was to determine the risk factors for CHD events in Polyclinic of South Solok Hospital. This research an analytical survey research with a case control design. The sample in this study consisted of a case group, namely patients suffering from CHD and a control group, namely patients who did not suffer from CHD, the total sample was 80 respondents with a ratio of 1: 1. Data processing using a computer application, namely SPSS, uses Chi-square statistical test analysis. The results of the univariate analysis showed that 71.2% of respondents had hypertension, 38.8% had DM, 51.2% were obese, and 15% of respondents were smoking. The results of the bivariate analysis had a relationship between hypertension and CHD (p value = 0.003), there was no relationship between DM and CHD (p value = 0.359), there was a relationship between obesity and CHD (p value = 0.02), and there was no relationship between smoking with CHD (p value = 0.348). To conclude hypertension and obesity are risk factors for CHD in the Heart Poly of South Solok Hospital. It is expected in respondents to maintain health by maintaining blood pressure, and weight to avoid the occurrence of CHD.